Efficacy of a Combined Antiplatelet Therapy Is Not Affected by a Simultaneous Binding of Cangrelor and PSB 0777 to Albumin - Wzorek, Joanna; Bednarek, Radosław; Watala, Cezary; Boncler, Magdalena (Frontiers in Pharmacology, 2021)
Concurrent administration of two drugs may complicate the management of acute coronary syndromes: competitive drug displacement diminishes drug binding and alters drug pharmacodynamics. We investigated the interaction of two antiplatelet compounds (PSB 0777 and cangrelor) with human serum albumin (HSA) to determine whether they compete with one another for the binding to albumin. Both examined compounds have been earlier claimed to bind to HSA (PSB 0777) or plasma proteins (cangrelor). Fluorescence spectroscopy, surface plasmon resonance spectroscopy and molecular modeling indicated that PSB 0777 and cangrelor interacted with HSA with moderate affinity (104 ‒ 105 M-1). The binding of cangrelor to HSA involved van der Waals interactions and hydrogen bonds, while the interaction of PSB 0777 with HSA was primarily driven by hydrophobic forces. It was found that PSB 0777 and cangrelor do not share the same binding site on the protein. Our findings highlight the importance of albumin in the transport of PSB 0777 and cangrelor and suggest that the antiplatelet activity of the examined compounds used in combination is not affected by competition-induced changes in drug binding to HSA.